2017
DOI: 10.1159/000472706
|View full text |Cite
|
Sign up to set email alerts
|

Favourable Outcome in a 33-Year-Old Female with Acute Haemorrhagic Leukoencephalitis

Abstract: Background: Acute haemorrhagic leukoencephalitis (AHLE) is a rare and rapidly fatal disease of unknown aetiology. There is a paucity of literature on the presentation and management of this rare disease. Case Description: We report the case of a 33-year-old female presenting with headache and left-sided apraxia. Imaging revealed a right-sided white matter lesion with extensive cytotoxic oedema. Pathology was suggestive of AHLE. She underwent an open excisional biopsy and was treated with high-dose corticostero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 12 publications
(27 reference statements)
2
18
0
Order By: Relevance
“…AHLE is a rare demyelinating condition with significant associated mortality ( Fontoura et al., 2002 ). It has previously been reported as a complication of other viral illnesses ( Solis et al., 2017 ). AHLE is thought to be the most fulminant variant of acute disseminated encephalomyelitis (ADEM) with rapid progression of white matter inflammation ( Rawal et al., 2019 ).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…AHLE is a rare demyelinating condition with significant associated mortality ( Fontoura et al., 2002 ). It has previously been reported as a complication of other viral illnesses ( Solis et al., 2017 ). AHLE is thought to be the most fulminant variant of acute disseminated encephalomyelitis (ADEM) with rapid progression of white matter inflammation ( Rawal et al., 2019 ).…”
Section: Discussionmentioning
confidence: 93%
“…Although the haemorrhagic component of AHLE is usually small, we believe in our case, this was severe enough to be depicted by CT due to possible aggravation effects of anticoagulation and hypertension. The pathophysiology of AHLE is not known but cross reactivation of host myelin and viral antigens is thought to be one possible mechanism ( Fontoura et al., 2002 ; Solis et al., 2017 ; Duggal et al., 2014 ). Moreover, reported cases of COVID-19 related diffuse leukoencephalopathy and microhaemorrhages have been thought to be likely in association with hypoxaemia ( Radmanesh et al., 2020a ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in our review of the literature, we found an overall mortality of 46.5%, which is substantially lower. Moreover, 14% of patients made a full recovery and returned to their premorbid neurological baseline ( 3 , 5 , 7 , 14 , 18 , 35 ), and 11% survived with only minor neurological sequelae ( 2 , 12 , 15 , 23 , 38 ). The reason for the better outcome in this systematic review compared to previous studies ( 3 , 4 ) remains unclear.…”
Section: Discussionmentioning
confidence: 99%